Ecological crises in higher education: making biodiversity matter for business students through critical thinking and interdisciplinary approaches - Kopnina, Helen; Baranowski, Mariusz; Russell, Mike (Society Register, 2025)
Biodiversity loss is accelerating at an alarming rate, posing significant challenges for sustainability, yet it remains inadequately addressed in business management education. Current sustainability pedagogies in business schools are predominantly anthropocentric, overlooking the biodiversity and extinction crises. This study examines the limitations of these approaches, particularly their failure to incorporate ecocentric perspectives and interdisciplinary methods critical for a comprehensive understanding of biodiversity. To address this gap, this paper integrates intra-, inter-, and transdisciplinary perspectives, offering a framework that challenges traditional, siloed approaches to business education. This research aims to bridge the gap between business education and biodiversity. We use secondary-data-based case studies of organizations and institutions of higher learning that offer business/corporate or executive education. This paper demonstrates how an ecocentric curriculum can more comprehensively address biodiversity challenges in sustainability education by examining case studies and incorporating insights from fields including psychology, natural sciences, and social sciences. Key findings indicate that traditional business curricula lack the depth needed to tackle complex ecological issues, and integrating interdisciplinary approaches enhances students’ understanding of biodiversity’s role in sustainability. We conclude that reimagining Education for Sustainable Development (ESD) within business schools through an ecocentric framework is essential. This shift transcends disciplinary boundaries and fosters ethical leadership capable of addressing the complexities of biodiversity loss, contributing to more holistic sustainability education.